(untitled) (Physical Education, Health and Social Sciences, 2025)
The current study emphasized its attention to develop an indigenous scale on Patient’s satisfaction with medical care in Urdu language. The scale was developed with purpose to illuminate the satisfaction level of patients from their respective doctors, staff and facilities provided to them in hospital where they are being treated. Age range for scale was 30-60 years. Patients admitted and being treated were considered for evaluation only. The initial draft was prepared through literature’s assistance, experts’ opinion, interviews and personal observations. Piloted study was also conducted to estimate the length and effectiveness of items. After piloting study, exploratory factor analysis was done via SPSS and principal component analysis was also applied. The cronbach’s alpha of three-factor model was .94. KMO and Bartlett’s test also explicates its reliability. Two factors named quality and comfort of health care facilities, wait time and finance were conducted after the analysis on the basis of literature review. Items total correlation was also evaluated. Exploratory factor analysis was done to extract the factors, factor structure and to finalize the items. Principal component analysis was done with varimax rotation method. The analysis explicated the scale’s reliability that the scale is reliable and valid for patients admitted in medical care unit. After exploratory factor analysis confirmatory factor analysis was done with AMOS 22 to confirm the scale’s reliability it also illustrated that scale is reliable. For estimating reliability, test-retest method and convergent validity was done. The results revealed that the test is valid and reliable. The findings revealed that scale is the best measure for research purpose and for clinical administrations.